TEACHERS WHO TEACH MATHEMATICS IN ADULT EDUCATION: CONCEPTS AND TEACHING PRACTICES - Andréa Thees; Maria Cecilia Fantinato (Editora da Universidade de Santa Cruz do Sul, 2012)
This work represents a subset of a Masters' research, which investigated how the pedagogical and non-pedagogical professional practices of mathematics teachers who teach in adult education are developed. In this paper we present the curricular management practices, tasks and materials, communication and evaluation. Through a case study of the daily activities of three math teachers who teach young people and adults, a qualitative research was developed, whose investigative tools were field observations, semi-structured interviews and questionnaires. Our study indicated that curriculum management practices are determined by a straightforward exposition teaching style, based on problem solving. Regarding the proposed tasks, teachers do not resort to learning materials other than blackboard and chalk, and rarely use the textbook. Communication in the classroom is univocal, sometimes supplemented by inadequate metaphors, especially in the teaching of algebra. The practices of student evaluation are predominantly focused on the summative function.